Respuesta :
Answer:
Correct choice is A
Step-by-step explanation:
1 step. Multiply [tex]x-5[/tex] by [tex]2x^2[/tex] to get [tex]2x^3-10x^2[/tex] and subtract this polynomial from the polynomial [tex]2x^3-13x^2+16x-5:[/tex]
[tex]2x^3-13x^2+16x-5-(2x^3-10x^2)=2x^2-13x^2+16x-5-2x^3+10x^2=-3x^2+16x-5.[/tex]
2 step. Multiply [tex]x-5[/tex] by [tex]-3x[/tex] to get [tex]-3x^2+15x[/tex] and subtract this polynomial from the polynomial [tex]-3x^2+16x-5:[/tex]
[tex]-3x^2+16x-5-(-3x^2+15x)=-3x^2+16x-5+3x^2-15x=x-5.[/tex]
3 step. Multiply [tex]x-5[/tex] by [tex]1[/tex] to get [tex]1[/tex] and subtract this polynomial from the polynomial [tex]x-5:[/tex]
[tex]x-5-(x-5)=x-5-x+5=0.[/tex]
Then
[tex]2x^3-13x^2+16x-5=(x-5)(2x^2-3x+1).[/tex]
Answer:
Correct answer is 2x2 − 3x + 1
Step-by-step explanation: